Clinical and Neurochemical Effects of Transcranial Magnetic Stimulation (TMS) in Multiple Sclerosis: A Study Protocol for a Randomized Clinical Trial - Agüera, Eduardo; Caballero-Villarraso, Javier; Feijóo, Montserrat; Escribano, Begoña M.; Conde, Cristina; Bahamonde, María C.; Giraldo, Ana I.; Paz-Rojas, Elier; Túnez, Isaac (Frontiers in Neurology, 2020)
Background: Transcranial Magnetic Stimulation (TMS) is a technique based on the principles of electromagnetic induction. It applies pulses of magnetic radiation that penetrate the brain tissue, and it is a non-invasive, painless, and practically innocuous procedure. Previous studies advocate the therapeutic capacity of TMS in several neurodegenerative and psychiatric processes, both in animal models and in human studies. Its uses in Parkinson's disease, Alzheimer's disease and in Huntington's chorea have shown improvement in the symptomatology and in the molecular profile, and even in the cellular density of the brain. Consequently, the extrapolation of these TMS results in the aforementioned neurodegenerative disease to other entities with etiopathogenic and clinical analogy would raise the relevance and feasibility of its use in multiple sclerosis (MS). The overall objective will be to demonstrate the effectiveness of the TMS in terms of safety and clinical improvement, as well as to observe the molecular changes in relation to the treatment. Methods and Design: Phase II clinical trial, unicentric, controlled, randomized, single blind. A total of 90 patients diagnosed with relapsing-remitting multiple sclerosis (RRMS) who meet all the inclusion criteria and do not present any of the exclusion criteria that are established and from which clinically evaluable results can be obtained. The patients included will be assigned under the 1:1:1 randomization formula, constituting three groups for the present study: 30 patients treated with natalizumab + white (placebo) + 30 patients treated with natalizumab + TMS (1 Hz) + 30 patients treated with natalizumab + TMS (5 Hz). Discussion: Results of this study will inform on the efficiency of the TMS for the treatment of MS. The expected results are that TMS is a useful therapeutic resource to improve clinical status (main parameters) and neurochemical profile (surrogate parameters); both types of parameters will be checked. Ethics and Dissemination: The study is approved by the Local Ethics Committee and registered in https://clinicaltrials.gov (NCT04062331). Dissemination will include submission to a peer-reviewed journal, patients, associations of sick people and family members, healthcare magazines and congress presentations. Trial Registration:ClinicalTrials.gov ID: NCT04062331 (registration date: 19th/ August/2019). Version Identifier: EMTr-EMRR, ver-3, 21/11/2017.